Refugees And Patronage: A Political History Of Uganda's 'Progressive' Refugee Policies. Issue 479 (8th April 2021) - Betts, Alexander
Abstract: Uganda's self-reliance policy for refugees has been recognized as among the most progressive refugee policies in the world. In contrast to many refugee-hosting countries, it allows refugees the right to work and freedom of movement. It has been widely praised as a model for other countries to emulate. However, there has been little research on the politics that underlie Uganda's approach. Why has Uganda maintained these policies despite hosting more refugees than any country in Africa? Based on archival research and elite interviews, this article provides a political history of Uganda's self-reliance policies from independence to the present. It unveils significant continuity in both the policies and the underlying politics. Refugee policy has been used by Ugandan leaders to strengthen patronage and assert political authority within strategically important refugee-hosting hinterlands. International donors have abetted domestic illiberalism in order to sustain a liberal internationalist success story. The politics of patronage and refugee policy have worked hand-in-hand. Patronage has, in the Ugandan case, been integral to the functioning of the international refugee system. Rather than being an inevitably 'African' phenomenon or the unavoidable legacy of colonialism, patronage politics has been enabled by, and essential to, liberal internationalism.